How do cultural elements shape speak-up behavior beyond the patient safety context? An interprofessional perspective in an obstetrics and gynecology department - Malik, Romana F.; Azar, Poyan; Taimounti, Achraf; Buljac-Samardžić, Martina; Hilders, Carina G. J. M.; Scheele, Fedde (Frontiers in Medicine, 2024)
Introduction Interprofessional working and learning thrives with speak-up behavior. Efforts to improve speak-up have mainly focused on isolated techniques and training programs within the patient safety scope, yet sustained improvement requires a cultural shift beyond this scope. This research investigates the influence of culture elements on speak-up behavior in interprofessional teams beyond the patient safety context. Methods An exploratory qualitative study design was used in a Dutch hospital's Obstetrics and Gynecology department. A representative sample of stakeholders was purposefully selected, resulting in semi-structured interviews with 13 professionals from different professional backgrounds (nurses, midwifes, managers, medical specialists, and residents). A speak-up pledge was developed by the research team and used to prime participants for discussion. Data analysis involved three-step coding, which led to the development of themes. Results This study has identified six primary cultural themes that enhance speak-up behavior. These themes encompass the importance of managing a shared vision, the role of functional hierarchy, the significance of robust interpersonal relationships, the formulation of a strategy delineating when to speak up and when to exercise restraint, the promotion of an open-minded professional mindset, and the integration of cultural practices in the context of interprofessional working and learning. Conclusions Six crucial cultural elements have been pinpointed to boost the practice of speaking up behavior in interprofessional working and learning. Remarkably, hierarchy should not be held responsible as the wrongdoer; instead, can be a great facilitator through respect and appreciation. We propose that employing transformational and humble leadership styles can provide guidance on effectively integrating the identified cultural elements into the workplace and provide an IMOI framework for effective interprofessional speak-up beyond patient safety.